Enhancing broiler growth and carcass quality: impact of diets enriched with Moringa oleifera leaf powder conjugated with zinc nanoparticles - Mohammed M. El-Abbasy; Ahmed K. Aldhalmi; Elwy A. Ashour; Samar S. Bassiony; Mahmoud Kamal; Abdulmohsen H. Alqhtani; Diaa E. Abou-Kassem; Ahmed A. Elolimy; Mohamed E. Abd El-Hack; Ayman A. Swelum (Poultry Science)
This study evaluated the effects of Moringa oleifera leaf powder extract stabilized with zinc nanoparticles (ZnNPs-MLPE) as a natural growth promoter in broiler diets. Randomly assigned 264 one-day-old Ross 308 chicks to four different feeding treatments, with each group being subdivided into six replicates, each comprising 11 unsexed chicks. The control group was fed a basic diet without additives, while the experimental groups were supplemented with 1.0, 2.0, or 3.0 cm³ of ZnNPs-MLPE/L of diet. The findings demonstrated that 2.0 and 3.0 cm³/L ZnNPs-MLPE supplementation significantly enhanced live body weight (LBW) and weight gain (BWG). Feed intake (FI) and feed conversion ratio (FCR) did not show significant differences between the treated groups and the control, indicating that the additive did not negatively affect feed efficiency. However, an increase in abdominal fat was noted in the ZnNPs-MLPE treatments relative to the control. Blood analysis revealed that the ZnNPs-MLPE groups had significantly lower levels of ''total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), very low-density lipoprotein (VLDL), and alanine transaminase (ALT) compared to the control group. In contrast, total protein (TP), albumin, and the albumin/globulin (A/G) ratio'' were higher in the ZnNPs-MLPE groups. Immunoglobulins IgY and IgM, as well as superoxide dismutase (SOD) levels, were elevated. Malondialdehyde (MDA) levels were reduced, indicating improved antioxidant capacity and immune function in the ZnNPs-MLPE-treated groups. In conclusion, supplementation with ZnNPs-MLPE at 2.0 and 3.0 cm³/L positively impacted broiler growth efficiency, antioxidant capacity, and immunological functionality. These findings support the potential of ZnNPs-MLPE as an effective natural growth enhancer for producing healthier poultry products.